Opinions and Attitudes of the Head of the Office of Religious Affairs in the City of Banjarmasin Regarding Lawsuits for Marriages During the Iddah Period which Have Been Inkracht - Fadillah, Muhammad Amin (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2023)
ABSTRACT This research is based on cases of marriages with an iddah term of fewer than 90 days but already inkracht as confirmed in the decision 230/Pdt.G/2022/PA.Bjm. The Head of the Office of Religious Affairs recorded the decision to continue the process. Initial observations of many Offices of Religious Affairs (KUA) in Banjarmasin show that each has a different approach to this issue. This seeks the Head of the Office of Religious Affairs (KUA)'s views on the marriage confirmation litigation during the iddah period, which is already inkracht. The Head of Banjarmasin's Office of Religious Affairs' rationale and legal foundation. This qualitative empirical legal research produces analytical descriptive data. Observation and interviews collected data. The Office of Religious Affairs (KUA) in North, West, and Central Banjarmasin has three heads. The purpose is Banjarmasin's Office of Religious Affairs Head's Opinion and Attitude. Research findings: from 3 informants who argued, the Head of the Central Banjarmasin Religious Affairs Office (KUA) attempted to confirm by examining documents related to marriage certificate issuance and coordinating with the court as a precaution in processing the marriage certificate results based on PP No. 9 of 1975 Article 6 paragraph (2). Based on Article 1 paragraph 1 of Law Number 22 of 1946, the Head of the West Banjarmasin Religious Affairs Office (KUA) believes that following court orders without confirmation or re-examination is acceptable. Based on article 24 Paragraph 1 of the 1945 Law, the Banjarmasin Religious Affairs Office (KUA) head also tends towards this. The registrar registers them if they follow the procedures. Repeat the marriage contract if ordered, emphasising that there is no confirmation. Keywords: Opinions, Attitudes, Marriage Isbat, Iddah, Inkracht ABSTRAK Penelitian ini didasarkan pada kasus perkawinan yang masa iddahnya kurang dari 90 hari namun sudah inkracht sebagaimana dikukuhkan dalam putusan 230/Pdt.G/2022/PA.Bjm. Kepala Kantor Agama mencatat keputusan melanjutkan proses tersebut. Pengamatan awal terhadap berbagai Kantor Urusan Agama (KUA) di Banjarmasin menunjukkan bahwa masing-masing Kantor Urusan Agama (KUA) mempunyai pendekatan berbeda terhadap persoalan ini. Hal ini untuk mencari pandangan Kepala Kantor Agama (KUA) terhadap gugatan pengukuhan perkawinan pada masa iddah yang sudah inkracht. Dasar pemikiran dan landasan hukum Kepala Kantor Agama Banjarmasin. Penelitian hukum empiris kualitatif ini menghasilkan data deskriptif analitis. Observasi dan wawancara mengumpulkan data. Kantor Urusan Agama (KUA) Banjarmasin Utara, Barat, dan Tengah mempunyai tiga kepala. Maksudnya adalah Pendapat dan Sikap Kepala Kantor Agama Banjarmasin. Temuan penelitian: dari 3 informan yang berargumen, Kepala Kantor Agama (KUA) Banjarmasin Pusat berupaya melakukan konfirmasi dengan memeriksa dokumen terkait penerbitan akta nikah dan berkoordinasi dengan pihak pengadilan sebagai langkah pencegahan dalam pengurusan hasil akta nikah berdasarkan PP No. 9 Tahun 1975 Pasal 6 ayat (2). Berdasarkan Pasal 1 ayat 1 Undang-Undang Nomor 22 Tahun 1946, Kepala Kantor Agama (KUA) Banjarmasin Barat berpendapat, mengikuti perintah pengadilan tanpa konfirmasi atau pemeriksaan ulang dapat diterima. Berdasarkan pasal 24 Ayat 1 UU Tahun 1945, Kepala Kantor Urusan Agama (KUA) Banjarmasin pun cenderung demikian. Panitera mendaftarkannya jika mengikuti prosedur. Ulangi akad nikah jika diperintahkan, tekankan bahwa tidak ada konfirmasi. Kata Kunci : Pendapat, Sikap, Isbat Nikah, Iddah, Inkracht